The Challenges Of Constructing The Connectivity Between Indonesia And Malaysia In The Malacca Strait - Irewati, Awani (Journal of Indonesian Social Sciences and Humanities, 2020)
One of the strategic and crustal sea lanes in Asia Pacific is the Malacca straits that separates the opposing coasts, between the Indonesia’s island of Sumatera and the Malay Peninsula. This dynamic strait has pushed the pulse of maritime economy of the two countries No exception for people to people relationship have been closely intertwined long time ago. In this case, Medan and Dumai of Sumatera Island in Indonesia are the two cities which have traditionally established people to people interaction with Penang and Melaka cities of Malaysia. This kind of interaction have been formalized under the framework of IMT-GT and the ASEAN Community. By the two frameworks, this interaction is put under the pillar of people to people connectivity. In the context of these two cooperation, there are three elements inherent in the connectivity concept, namely “infrastructures”, “institutions” and “people to people”. Medan and Dumai of Sumatera island still continue to build up the desired connectivity as the maritime corridor remains a major challenge for strengthening the connectivity between Malaysia and Indonesia. This paper aims at scrutinizing the main quest, which focuses on the challenges faced by Indonesia in constructing the maritime connectivity with Malaysia in the Malacca Strait. Through field research of IMT-GT context and the qualitative analysis, the paper is in favor of the argument that the Indonesia’s maritime corridors (Dumai and Medan) have not built adequately. In this regard, the government should streamline the management system linked to the internal connectivity issue.